2008
DOI: 10.1017/s0021859608007855
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative growth, superoxide dismutase activity and ion concentration of salt-stressed watermelon as influenced by rootstock

Abstract: SUMMARYWatermelon is a crop with a high water demand and is frequently grown under conditions of higher than normal root-zone salinity. In the present study, seedlings of watermelon (cv. Fantasy, Citrullus lanatus (Thunb.) Matsum & Nakai) were grown either ungrafted or grafted on three rootstocks: Strong Tosa, S1 (both Cucurbita maxima×Cucurbita moschata), or Emphasis (Lagenaria siceraria). All the plants were exposed to an NaCl-induced salinity stress (electrical conductivity, EC=2·2, 4·0, or 6·0 dS/m). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 43 publications
4
37
2
2
Order By: Relevance
“…Furthermore, the grafted plants (with Maxifort rootstock) did not exclude Cl -more efficiently than the nongrafted plants. These results are in contrast to those reported earlier for other grafting combinations of Jaguar cv tomato (Estan et al, 2005), watermelon (Goreta et al, 2008), and cucumber (Huang et al, 2009). They all reported that grafting decreased Cl -(as well as decreased Na + and higher yields) as compared to nongrafted under salt stress.…”
Section: Leaf Ion Compositioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the grafted plants (with Maxifort rootstock) did not exclude Cl -more efficiently than the nongrafted plants. These results are in contrast to those reported earlier for other grafting combinations of Jaguar cv tomato (Estan et al, 2005), watermelon (Goreta et al, 2008), and cucumber (Huang et al, 2009). They all reported that grafting decreased Cl -(as well as decreased Na + and higher yields) as compared to nongrafted under salt stress.…”
Section: Leaf Ion Compositioncontrasting
confidence: 99%
“…These data indicate that increased Na + concentrations have a role in the response of tomato to salt stress. Earlier, Estan et al (2005) for tomato, Goreta et al (2008) Grafted and nongrafted plants had comparable Cl -leaf concentrations, as shown in Table 3 (only one salinity level was statistically significantly different). These data indicate that Cl -accumulation does not explain the greater yield of grafted tomato plants as compared to nongrafted plants under saline conditions.…”
Section: Leaf Ion Compositionmentioning
confidence: 70%
See 2 more Smart Citations
“…Yasar, Uzal and Yasar (2013) carried out a study examining the salt stress-tolerance of watermelon genotypes and indicated that the plants selectively took up Na + and K + ion under salt stress conditions, and the resistant genotypes promoted the uptake of K + ions rather than Na + ions. Moreover, under salinity stress conditions, with increasing salt concentration, the K + ion concentration increases in salt tolerant plants (Goreta et al, 2008;Yetisir;Uygur, 2009). Therefore, the K/Na ratio represents the tolerance level of a genotype.…”
Section: Effect Of Salt Stress On Plant Nutrient Contents Of Watermelmentioning
confidence: 99%